Profile of gestational syphilis in the state of Paraná between 2010 and 2018 - Hayashida, Mariana Rie; Hirota, Michely Mika; Mizoguti, Nathália Nakase; Ito, Fernanda Yuki; Gonçalves, Maryna Rodrigues; Nasr, Acácia Maria Lourenço Franscisco (Brazilian Journal of Sexually Transmitted Diseases, 2020)
Introduction: Gestational syphilis is responsible for increased fetal morbidity and mortality. It is related to intrauterine and neonatal complications, with vertical transmission being the most severe outcome. Screening and treatments are part of the prenatal routine. Objective: To describe the profile of gestational syphilis by state, regional incidence, time of diagnosis and treatment. Methods: Quantitative, descriptive, and observational study developed with secondary data from the National System of Notification of Disorders (Sistema de Informação de Agravos de Notificação – SINAN), to evaluate the variables: region, trimester of diagnosis and treatment of gestational syphilis. Results: Between 2010–2018, Paraná recorded 12,011 cases of gestational syphilis, corresponding to 8.5 per 1,000 live births. There was an increase in the number of cases across the state. Among infected pregnant women, most were between 20–29 years old (50.6%). Of the diagnoses, 43.6% were performed in the first trimester of pregnancy and 26.6% in the second. The most widely used treatment regimen was benzathine penicillin G 7,200,000 IU (63.7%). Conclusion: There was an increase in gestational syphilis in Paraná, however, there was greater effectiveness in diagnosis and treatment, with greater detection in the first trimester of pregnancy and prevalence of use of benzathine penicillin G. The study highlights the importance of correct clinical management and early detection, measures that prevent vertical transmission.